Pelatihan Pemanfaatan Microsoft Office (Word, PowerPoint, Excel) Kepada Siswa SMAS Bodhi Dharma - Holong Marisi Simalango (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2023)
Software utilization is part of the use of technology, especially in the field of education, which can be used as a provision in the field of work and further education. Community Service at SMAS Bodhi Dharma which is a private high school located in Batam City. The online transition to offline learning at school after being declared a Covid-19 endemic has returned teaching and learning activities using school facilities. The purpose of this service activity is to provide insight, basic understanding, and application of Microsoft Office products, especially in Word, PowerPoint, and Excel products. The methods used in this service are interviews and surveys with the Principal of SMAS Bodhi Dharma, participant data surveys, material preparation, training practices, and evaluation. The training participants were students from different classes totalling 40 people. This training was conducted offline for two days. The results of this training are seen from the results of the evaluation work that is by the questions given. Participants were also very enthusiastic during the training and it is hoped that the next training program will provide advanced skills training in the use of Microsoft Office (Word, PowerPoint, Excel).